1997
DOI: 10.1046/j.1365-2168.1997.02543.x
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant intraoperative photodynamic therapy in experimental colorectal cancer using a new photosensitizer

Abstract: AIOPDT using either Photofrin or m-THPC was equally effective in reducing local recurrence in this model. Since treatment time with m-THPC was only 25 s compared with 11 min with Photofrin, the use of the former new photosensitizer increases the practicality of AIOPDT and could enable the laser to be replaced with cheaper, less intense light sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…It can be prepared as a chemically pure compound, it shows enrichment in tumor versus normal tissue and has an absorption maximum at 650 nm, redshifted compared to HpD which means deeper light penetration. In addition, mTHPC requires smaller quantities for administration, shorter treatment times and a lower light dose to achieve the desired PDT response (45).…”
Section: Synthesis Characterization and Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be prepared as a chemically pure compound, it shows enrichment in tumor versus normal tissue and has an absorption maximum at 650 nm, redshifted compared to HpD which means deeper light penetration. In addition, mTHPC requires smaller quantities for administration, shorter treatment times and a lower light dose to achieve the desired PDT response (45).…”
Section: Synthesis Characterization and Detectionmentioning
confidence: 99%
“…In another study with murine colorectal cancer implanted mice it was shown that the highest tumor:tissue ratios after 4 days were found for the small intestine, liver and skeletal muscle (134). This animal model was used as a general test bed for PDT assessment (271) and for AIOPDT (45). A study of healthy hamsters showed highest drug levels in the gastric and duodenal mucosa and acinar pancreas after 2-4 days (272).…”
Section: Animal Modelsmentioning
confidence: 99%
“…The combination of amphiphilic and favorable photophysical properties of m-THPC leads to highly selective and effective tumor destruction (5). In comparative studies of m-THPC and Photofrin, m-THPC was found to be more effective because similar therapeutic results were obtained with shorter treatment times and much lower doses (6). The m-THPC has been reported to be 20-fold more active than HpD (7).…”
Section: Introductionmentioning
confidence: 94%
“…Whereas this small clinical study may have been underpowered statistically, no improvement in the rate of local recurrence or survival was noted in the group treated with PDT. 91,92 Anecdotally, our group has used porfimer sodium PDT in patients previously treated with chemo-radiation therapy. Three patients with esophageal adenocarcinoma were ''downstaged'' with radiation and chemotherapy, allowing PDT to successfully eradicate the remaining neoplasm on the mucosal surface.…”
Section: Pdt As Adjuvant Treatment After Surgery or Chemo-radiationmentioning
confidence: 99%
“…Other photosensitizers have been tried in animal studies, but no clinical results have yet been published. 91 Other potential treatment strategies include the use of photoimmunoconjugates for selective photosensitizer delivery to target metastatic liver lesions. 146,147 Still other investigators are studying the variable response to PDT for colorectal tumors that may lack certain oncogenes such as p53.…”
Section: Pdt For Colorectal Cancermentioning
confidence: 99%